(untitled) (Journal of the College of Basic Education, 2022)
The phenomenon of violence is one of the manifestations of modern life, but it is the most obvious and influential aspect of human life. It is a phenomenon with psychological, social, religious, political, economic and legal dimensions that interact, appear and practice in forms and images that distort the features of humanity (Ghanima, 2004: 311).Abdel Samad (2002) believes that violence destroys social relations and eliminates the basis of social construction, obstructs the development process, and impedes security and social readiness (Abdul Samad, 2002: 198).Ismail (2005) confirms that the phenomenon of violence is no longer just a threat to the state and the ruling regime, but rather has become a threat to the entire society, whether in its internal environment, economy, social and political security, and its cultural and intellectual gains (Ismail, 2005: 141).